2013
DOI: 10.1002/mrm.24977
|View full text |Cite
|
Sign up to set email alerts
|

Free‐breathing cardiac MR stress perfusion with real‐time slice tracking

Abstract: Purpose To develop a free-breathing cardiac MR perfusion sequence with slice tracking for use after physical exercise. Methods We propose to use a leading navigator, placed immediately before each 2D slice acquisition, for tracking the respiratory motion and updating the slice location in real-time. The proposed sequence was used to acquire CMR perfusion datasets in 12 healthy adult subjects and 8 patients. Images were compared with the conventional perfusion (i.e. without slice tracking) results from the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Commonly, those acquisitions use respiration navigator tracking that discard images that are outside the navigator acceptance window, which typically achieve acceptance efficiencies between 30% and 50%. However, recently there have been significant advances in increasing two‐dimensional or three‐dimensional scan efficiency up to 100% (i.e., using data of the entire respiratory cycle) for coronary MR angiography , cardiac perfusion , or cardiac CINE acquisitions while prospectively or retrospectively correcting for respiratory motion. Weingartner et al reported a three‐dimensional cardiac T 1 mapping approach that uses 100% scan efficiency for outer k‐space lines and a reduced efficiency on the inner k‐space part.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, those acquisitions use respiration navigator tracking that discard images that are outside the navigator acceptance window, which typically achieve acceptance efficiencies between 30% and 50%. However, recently there have been significant advances in increasing two‐dimensional or three‐dimensional scan efficiency up to 100% (i.e., using data of the entire respiratory cycle) for coronary MR angiography , cardiac perfusion , or cardiac CINE acquisitions while prospectively or retrospectively correcting for respiratory motion. Weingartner et al reported a three‐dimensional cardiac T 1 mapping approach that uses 100% scan efficiency for outer k‐space lines and a reduced efficiency on the inner k‐space part.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, this is one of the major technical limitations of CMR perfusion after physical stress. In order to address postexercise respiratory motion during perfusion imaging, our method incorporated a diaphragmatic respiratory navigator tracking in combination with slice following to reduce the respiratory‐induced motion . A fixed tracking factor of 0.6 was used for all subjects and may have limited the performance of the slice tracking technique .…”
Section: Discussionmentioning
confidence: 99%
“…An improved slice tracking technique was used for both rest and exercise stress perfusion protocols. In this approach, the location of each slice is adjusted independently based on a two‐dimensional pencil beam navigator acquired before the imaging pulses of each slice and a tracking factor of 0.6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the navigator has been used for ‘slice tracking’ the FPP slices to follow the respiratory motion of the heart. This was first demonstrated in FPP by Pedersen et al [ 119 ] and improved with application of a ‘navigator-restore’ pulse to maintain sufficient navigator signal when combined with the FPP saturation recovery sequence [ 120 ]. However, as it has to prospectively shift the slice-excitation based on the navigator information, there will always be concerns over its reliability, and a motion-correction model between the typical right-hemidiaphragmatic navigator and the short-axis slices should be employed; this procedure cannot currently be regarded as clinically routine.…”
Section: Motion Challengesmentioning
confidence: 99%